(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
In Uzbekistan, an important problem is the spread of chronic inflammatory processes in the nasal mucosa. Research shows that difficult climatic conditions and dietary habits of the population negatively affect the immune system and increase the incidence of respiratory tract inflammation. The incidence of ENT diseases is higher than average, and rhinosinusitis among children was registered in 23.7% [Pishenichnov S.I., 2021]. Research by Russian specialists, such as A. O. Gusan [2014], emphasizes the importance of timely diagnosis and treatment of pathologies of the paranasal sinuses, especially in children.